2020
DOI: 10.3390/en13174377
|View full text |Cite
|
Sign up to set email alerts
|

Study on Foamed Concrete Used as Gas Isolation Material in the Coal Mine Goaf

Abstract: In view of the serious threat of gas accumulation in the coal mine goaf and the limitations of the existing gas sealing materials, the orthogonal experiment was developed to study a new type of foamed concrete for mine gas sealing. Dry density, gas permeability, and compressive strength were studied as the material indicators according to the demands of the gas isolation material in the coal mine goaf, and the experimental results showed that foam content was the most important factor. Meanwhile, the optimum m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In recent years, researchers have applied this material to the goaf treatment field, providing advantages over traditional methods such as backfilling with solid materials or filling with water. It can be easily injected into the goaf through pipelines, filling up the space effectively, and thereby greatly reducing the risk of surface subsidence caused by goaf collapse [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have applied this material to the goaf treatment field, providing advantages over traditional methods such as backfilling with solid materials or filling with water. It can be easily injected into the goaf through pipelines, filling up the space effectively, and thereby greatly reducing the risk of surface subsidence caused by goaf collapse [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional goaf treatment ways, examples of these practices include backfilling using solid materials or filling techniques employing water, clay-cement composite grouting material and geopolymer grouting material have many advantages. For example, the material is conveniently inserted to gap via piping, effectively occupying goaf cavity as well as significantly mitigating the potential for surface subsidence resulting from goaf collapse (Xu et al, 2020;Shrestha et al, 2022). Wang et al proposed a new method of using coal gangue powder as the dominant component in grouting backfill materials for underground mining with optimized slurry transportability and compressive strength using urea and quicklime as additives (Wang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…With the utilization of coal resources, the mining intensity increases year by year, and the underground mining conditions become more complex, resulting in an increase in disasters and accidents, such as fires, explosions, and outbursts. , After a coal mine disaster, the rapid sealing and isolation control of the disaster area can effectively prevent further accidents. , To improve the mine emergency response ability to deal with disasters and accidents, scholars conducted relevant research on the technology and equipment for rapid closed isolation of disaster areas after disasters. Chang proposed a solidified door structure for a mine rescue cabin, established a three-dimensional model of a mine mobile protective closed door, and analyzed the strength of an arc door with ANSYS software. The results showed that the strength and stiffness of the arc door are better than those of the ordinary flat door.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 To improve the mine emergency response ability to deal with disasters and accidents, scholars conducted relevant research on the technology and equipment for rapid closed isolation of disaster areas after disasters. 5 7 Chang 8 proposed a solidified door structure for a mine rescue cabin, established a three-dimensional model of a mine mobile protective closed door, and analyzed the strength of an arc door with ANSYS software. The results showed that the strength and stiffness of the arc door are better than those of the ordinary flat door.…”
Section: Introductionmentioning
confidence: 99%